Third-Order Sliding Mode Control of Five-Phase Permanent Magnet Synchronous Motor Using Direct Torque Control Based on a Modified SVM Algorithm - Mehedi, Fayçal; Bouyakoub, Ismail; Yousfi, Abdelkader; Reguieg, Zakaria (International Journal of Robotics and Control Systems, 2025)
Direct Torque Control (DTC) is a powerful method for multiphase drive systems, offering significant performance and efficiency gains, but its implementation is challenged by complexities like uncertainties and disturbances. This research addresses these issues, particularly the variable switching frequencies of hysteresis controllers with switching table and the limitations of conventional proportional-integral (PI) controllers in the outer loop, to enhance DTC for superior control in multiphase drives. The study proposes an improved DTC technique for a five-phase permanent magnet synchronous motor (5Ph-PMSM). This strategy integrates a robust nonlinear third-order super-twisting sliding mode control (TOSMC) with a modified space vector modulation (MSVM) algorithm. The MSVM is based on calculating the minimum and maximum of the five-phase voltages, contributing to optimized performance. This proposed DTC-TOSMC-MSVM approach significantly outperforms conventional DTC (DTC-Conv). It achieves tighter control, substantially reducing flux and torque ripple, and minimizing response time. Furthermore, it lowers the total harmonic distortion (THD) and improves disturbance rejection. The merits of the proposed strategy of 5Ph-PMSM are demonstrated through various tests. MATLAB simulations confirm these benefits, showing an 88.88% reduction in speed response time compared to DTC-Conv. Additionally, the proposed method reduces flux ripple by 51.85%, torque ripple by 63.15%, and stator current THD by 61.08%. In addition, the proposed method demonstrates robust performance when faced with changes in machine parameters and load disturbances, making it superior to traditional DTC approaches.